THE ROLE OF DESBUMI IN FAMILY WELFARE ENHANCEMENT FOR FORMER MIGRANT WORKERS IN DUKUH DEMPOK VILLAGE WULUHAN SUB-DISTRICT JEMBER REGENCY - Sangidatus Sholiha (UPT Penerbitan Universitas Jember)
DESBUMI (Desa Peduli Buruh Migran) is one of the institutions which was established by the village government of Dukuh Dempok to show its concerns towards the migrant workers. Desbumi was initiated by the village government based on the various problems excavated in Dukuh Dempok village community. Some problems are the illegal migrant workers, the high divorce rate, the juvenile delinquency, the difficulty of ex-migrant workers in finding jobs after returning from abroad, the violence experienced by migrant workers by employers, etc. As taken from the problems mentioned above, the village government takes an action by consulting to the Migrant Care based in Jember to find out the way regarding to the problems. Next, the village government collects the migrant workers’ data in Dukuh Dempok, both the active workers and the the former workers who already gone back to homeland. Once the data are collected, the village government staff held a meeting to gather the former migrant workers and the migrant care. Through the meeting, the former migrant workers are given some knowledges, motivations and the understanding about the imigrant things. The meeting arises the finding of hidden problems such as the lack of chances for the fomer migrant workers to build the self development that leads them to turn unemployed once they are back to their homeland. Desbumi is established to provide the chances to improve the the welfare of Dukuh Dempok community. It also provides services of safe migration, handles the migration problems and community empowerment. Desbumi gives a very good role in protecting the migrant workers and the empowerment of former migrant workers as a form of awareness of the village government towards the former migrant workers. Based on the statement above, the empowerment training of former migrant workers held by Desbumi gives many good effects such as educating the villagers about the utilization of the surrounding resources, prospering families and communities, especially the members of citizens, creating jobs for former migrant workers and more empowered, and improving the economic matters of Dukuh Dempok community.